Theorizing STS from Asia—Toward an STS Multiscale Bioecology Framework: A Blurred Genre Manifesto/Agenda for an Emergent Field. Issue 4 (1st December 2018) - Fischer, Michael M. J.
Abstract: East Asia and Southeast Asia provide at least four relational locales or sites of cultural critique and materials for new twenty-first-century theory construction governed by growing biological and ecological knowledge. I document a moment in East Asian and Southeast Asian STS that grounds methodological advocacy for how anthropological STS initiatives revise received models and theories and how they work from multiple and differentiated Asian sites, thereby focusing on the importance of Asian examples in global theory without sliding into meaningless discussions of Asian essentialisms or East versus West orientalisms and occidentalisms. The four relational technoscientific sites and perspectives are those of (a) scientists as social hieroglyphs and peopled networks; (b) hidden curriculums and education reforms; (c) geoportraits of influencing machines, bioecological entanglements, and cultural flows; and (d) disaster and repair cycles, new and old cultural genres for coping, and structures of feelings. By citing the growing new anthropological STS ethnographic work in a variety of Asian locales, I suggest that new narratives and models are already out there as emergent forms of life, that is, as contested, shifting third spaces (forming in the interstices of old distinctions and categories) and ethical plateaus (terrains of decision making where multiple technological changes intersect and impose double-binds or trade-offs among simultaneous imperatives).